Looking Back on Two Decades of Poverty and Well-Being in India - Narayan, Ambar; Murgai, Rinku (World Bank, Washington, DC, 2016)
This paper provides an overview of poverty and well-being trends in India since the mid-1990s. Poverty reduction since 2005 has been much faster than the earlier decade, as a result of broad-based growth across most geographic areas. Underlying this is a pattern of high mobility in economic status that has led to an emerging middle class. Still, a vast (and rising) share of the population faces significant risk of slipping back into poverty. India's poor are increasingly concentrated in low-income states with historically lower rates of economic progress. Even as India has reduced poverty faster than the developing world as a whole, the degree of poverty reduction associated with growth has been substantially lower than in some of its middle-income peers. India faces important challenges in nonmonetary dimensions of welfare as well. Despite success on important fronts, such as infant and child mortality and secondary education, progress has been slow in others, such as sanitation and nutrition, and lags behind some other countries that are at a similar stage of development.